Integrasi Pendekatan Deep Learning dan Kearifan Lokal Menuju Era SDGs Berbasis Nilai Karakter - Rozhana, Kardiana; Zendha Avalentina, Kardiana; Tri Atmaja, Adi (Cartesian: Jurnal Pendidikan Matematika, 2026)
This study integrates Deep Learning and local wisdom to support the achievement of SDGs through character-based education in the Elementary School Teacher Education Program at Tribhuwana Tunggadewi University. The research responds to the growing need for innovative learning strategies that enhance mathematical literacy, strengthen character, and foster sustainability awareness. The study aims to develop a learning design for the Basic Mathematics course by combining Deep Learning with the cultural values of Malang City to cultivate students’ critical, creative, and ethical thinking. A qualitative case study approach was employed, involving classroom observations, interviews, and document analysis with 45 Elementary School Teacher Education Program students. Findings indicate that integrating Deep Learning and local wisdom increases student engagement, contextual understanding, cultural appreciation, and problem-solving skills, which were initially low. Character values such as responsibility, collaboration, and respect for diversity became more deeply internalized through the learning process. The study concludes that this approach effectively aligns higher education practice with the SDGs framework, particularly Goal 4 on quality education, through the integration of Deep Learning and cultural identity. This integration provides a sustainable pathway for teacher education in Indonesia.